Study on Li Metal Deposition, SEI Formation on Anodes and Cathode Potential Change during the Pre-Lithiation Process in a Cell Prepared with Laminated Porous Anodes and Cathodes. (19th June 2018) - Tsuda, Takashi; Ando, Nobuo; Haruki, Yusuke; Tanabe, Toyokazu; Gunji, Takao; Itagaki, Kaoru; Soma, Naohiko; Nakamura, Susumu; Hayashi, Narumi; Matsumoto, Futoshi
Abstract : The pre-doping of Li + ions (pre-lithiation) in graphite anodes, which is needed to improve the initial charging/discharging efficiency of lithium ion batteries, was examined from the viewpoints of lithium metal deposition, surface electrolyte interface (SEI) formation and electrode potential changes in the cathode during the pre-lithiation. Using a cell composed of pre-laminated, through-holed anodes and cathodes, the anodes were pre-lithiated with the perpendicular pre-doping method, as explained in this work, which can effectively enhance the pre-lithiation process in laminated cells. In the pre-lithiation system, Li deposition was not observed on the anode surfaces during pre-lithiation, and the thickness of the SEI layers formed on the anodes did not increase. Moreover, the SEI layer has the same composition as that formed by the electrochemical lithiation (charging) process, even when the pre-lithiation of the anodes is accelerated by through-holes formed on the anode and cathode electrodes. In addition, the electrode potential of cathodes inserted between pre-lithiated anodes does not change during the pre-lithiation process, and the capacity of the cathodes does not degrade upon pre-lithiation. The perpendicular pre-doping method examined in this study is found to be applicable to the production process of lithium ion batteries with high charging/discharging efficiency.